Elevated Expression of Growth Differentiation Factor-15 Is Associated With Acute Exacerbation of Idiopathic Pulmonary Fibrosis - Cao, Mengshu; Gu, Lina; Guo, Lili; Liu, Mengying; Wang, Tianzhen; Zhang, Ji; Zhang, Huizhe; Zhang, Yufeng; Shi, Yanchen; Zhao, Yichao; Qiu, Xiaohua; Gui, Xianhua; et al. (Frontiers in Immunology, 2022)
Background：Growth differentiation factor 15 (GDF-15) is a highly divergent member of the TGF-β superfamily and has been implicated in various biological functions. However, the expression of GDF-15 in patients with acute exacerbation of idiopathic pulmonary fibrosis (AE-IPF) is unclear. Methods：The present study included 47 AE-IPF patients, 61 stable IPF (S-IPF) patients and 31 healthy controls (HC). Serum GDF-15 levels and its expression in the lung tissues were measured. The correlation between serum GDF-15 and other clinical variables, and the risk factors for AE occurrence and survival were analyzed. Results: Serum GDF-15 levels were significantly elevated in AE-IPF patients (1279.22 ± 540.02 pg/ml) as compared with S-IPF subjects (891.30 ± 479.90 pg/ml) or with HC (107.82 ± 14.21 pg/ml) (both P < 0.001). The mRNA and protein expressions of GDF-15 in the lung of AE-IPF patients were greatly increased as compared to S-IPF or NC (P = 0.026 and P = 0.007, respectively). Serum GDF-15 level was correlated with the clinical variables such as inflammation, metabolism and disease severity (all P < 0.05). Serum GDF-15 level was significantly higher in decedents than in survivors (P = 0.005). Serum GDF-15 level above 989.3 pg/ml was a risk factor for AE occurrence (P = 0.04), and the level above 1075.76 pg/mL was an independent predictor of survival in IPF patients (P = 0.007). Conclusion：GDF15 level was significantly elevated in AE-IPF patients. GDF-15 could be a potential biomarker for predicting AE occurrence and survival in IPF.